Periodisitas Harian Kehadiran Walang Sangit (Leptocorisa oratorius F.) pada Kepiting yang Membusuk - Solikhin Solikhin; Edhi Martono (Jurnal Perlindungan Tanaman Indonesia, 1997)
To know daily periodicity attendance of rice bug (Leptocorisa oratorius F.) in response to sixth-day-decaying crab, an experiment was conducted in four consecutive days in May 1997 in Gamping, Special Territory of Yogyakarta. The experiment consisted of 17 treatments and 3 replications arranged in randomized completely block design. Seventeen hourly observations (treatments) were made on rice bugs attendance on the decaying crab by direct counting as well as the relative humidity and temperature from 5 am to 9 pm. The result of the experiment showed that the peaks of rice bug attendance were from 10 am to 6 pm, while the highest one was at 5 pm (20 rice bugs).